Professional educators in the Circumpolar North:A model for the digital competence of future teachers - Korte, Satu-Maarit; Körkkö, Minna; Maxwell, Gregor; Beaton, Mhairi; Keskitalo, Pigga; Hast, Miia; Kyrö-Ämmälä, Outi; Mommo, Sanna (2023)
This article is based on a study that considers future teachers’ digital competencies in the Arctic education context with special attention to the necessary cultural and contextual dimensions of teachers’ work. This study explored the professional competencies teachers require when teaching diverse and multicultural pupils in the Circumpolar North drawing on the multiple affordances offered by the digital world. Previous research draws attention to specific teaching and teacher competencies required for rural schools in the Circumpolar North considering the unique assets and characteristics of rural places in this region. This study presents a model of Digital Competence for Future Teachers (DCFT) that illustrates the competencies required by teachers in rural schools in the Arctic. Within the proposed model, four types of digital knowledge-based competencies necessary for holistic education were identified: techno-cultural, intercultural, self-cultural, and micro-cultural. The model was created through a process of analysis of existing models of teachers’ digital competencies: MAP-, TPACK- and PEAT-models which are then reflected on the findings of an earlier international comparative multiple-case study by the same authors examining the sudden change to remote online teaching during the COVID-19 pandemic, and the Cultural Competence for Equity and Inclusion (CCEI) framework. Although the presented study focused on the Circumpolar North, the findings have implications for teacher education and policy production more widely in national and international educational environments. This article is based on a study that considers future teachers’ digital competencies in the Arctic education context with special attention to the necessary cultural and contextual dimensions of teachers’ work. This study explored the professional competencies teachers require when teaching diverse and multicultural pupils in the Circumpolar North drawing on the multiple affordances offered by the digital world. Previous research ...